A study to observe the association of pupil-to-limbus diameter ratio with blood pressure and pulse rate in type 2 diabetic patients - Yuvraj Subramani Sagadevan; Shyma Parapurath; Goothy, Sai Sailesh kumar; Anita Choudhary; Rohit Singh Chouhan (Asian Journal of Medical Sciences, 2022)
Background: Understanding the autonomic activity in the early hand helps to begin with effective treatment for the benefit of the individual with type 2 diabetes. Aims and Objectives: The present study was undertaken to observe the association of pupil-to-limbus diameter ratio with blood pressure and pulse rate in type 2 diabetic patients. Materials and Methods: A total of 100 participants with type 2 diabetes were part of the study after obtaining written, voluntary, and informed consent. Recording of the pupil-to-limbus diameter (PLD) ratio was performed using two box method which is a standard method mentioned in the literature. Blood pressure and pulse rate were used using a diamond digital sphygmomanometer (BPDG024). Results: There was a significant (P<0.00001) positive correlation between the PLD ratio of the right eye and pulse rate. There was a significant (P<0.05) negative correlation between the PLD ratio of the right eye and systolic blood pressure (SBP). There was a significant (P<0.05) negative correlation between the PLD ratio of the right eye and diastolic blood pressure (DBP). There was a significant (P<0.00001) positive correlation between the PLD ratio of the left eye and pulse rate. There was a significant (P=0.000076) negative correlation between the PLD ratio of the left eye and SBP. There was a significant (P=0.000458) negative correlation between the PLD ratio of the left eye and DBP. Conclusion: The study results revealed a significant positive correlation between the PLD ratio of the right and left eye with the pulse rate. There was a significant negative correlation between the PLD ratio of the right and left eye with both systolic and DBP.